1917 Cal. Stat. 221, §§ 3-4 - (:unkn) unknown (My University, 1917)
Prohibited the concealed carry of any pistol, revolver, or other firearm without a license. Violators guilty of a misdemeanor. Also declared the unlawful carry or possession of any of the above items as a nuisance, to be confiscated by the police and surrendered to a judge. Confiscated weapons are to be destroyed at the end of the year.
Keywords: CARRY - CONCEALED